(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Litvinova Tatyana Alexandrovna The problem of stability and variability of author’s idiostyle refers to the number of less studied problems. In some works it is decided mainly on the material of works of art. The article presents the results of the pilot studies, of the stability/variability of quantitative parameters of the texts, which are samples of Russian natural writing. The texts were processed using the Russian version of the program Linguistic Inquiry and Word Count, developed by American scientists-psychologists. This program has been used successfully to study the problem of the relationship of language and identity on the material of a number of languages (English, German, Chinese, Italian, Arabic and others.), but in Russian material it has not been studied. The program estimates the proportion of words in the text of certain morphological and lexical-semantic categories. 1188 texts were analyzed by 594 respondents, and the methods of statistical analysis obtained coefficients of variation for each language parameters. It is highlighted text parameters being relatively stable in texts of one author, and the parameters that have high coefficients of variation-coefficient. The possibility of using the results of IC solutions for the following tasks of author study and prospects for further work are defined. Key words: stylemetrics, author study, idiostyle, written speech, attribution of the text, corpus.